Best Answer

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals".

Q: What is the answer to y 2x 2 2 -1?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

y=2x-4 y=2x-5 y=1 1=2x-4 -2x = -5 x=2/5 the solution is (x,y) = (2/5,1)

y = -1/(3x7 + 2x - 9)y = -(3x7 + 2x - 9)-1y' = -(-1)(3x7 + 2x - 9)-2(3x7 + 2x - 9)'y' = (3x7 + 2x - 9)-2(21x6 + 2)y' = (21x6 + 2)/(3x7 + 2x - 9)2

y-2x=3 -y -y -2x=3-y -3 -3 -2x-3=-y /-1 /-1 2x+3=y y=2x and y=2x+3 have the same slope of 2, so they are parallel. Hope this helps! ;D

2x / (y-2) + 2x / (2-y)First get a common denominator: (y-2) (2-y)Then you have:2x(2-y) / (y-2)(2-y) + 2x(y-2) / (y-2)(2-y), summing and simplifying, you get:(4x-4) / (y-2)(2-y)

2x-y -5 = 0 => y = 2x -5 The perpendicular slope is the negative reciprocal of 2 which is -1/2 So using the formula of y -y1 = m(x -x1) gives the straight line equation:- y - -2 = -1/2(x -4) y +2 = -1/2x +2 y = -1/2x +2 -2 y = -1/2x which can be expressed in the form of: x +2y = 0 So the straight line equation is: x +2y = 0

Related questions

y=2x-4 y=2x-5 y=1 1=2x-4 -2x = -5 x=2/5 the solution is (x,y) = (2/5,1)

2

-2x +4y = 8 4y = 2x +8 y = 1/2x +2 Therefore: the y intercept is 2 and the slope is 1/2

If you mean y = 2x+1 then the slope is 2 and the y intercept is 1

y = f(x) = (2x + 1)/(x - 1)y*(x - 1) = (2x + 1) xy - y = 2x + 1xy - 2x = y + 1x(y - 2) = y + 1so x = (y + 1)/(y - 2) assuming yâ‰?2.So the inverse function is f-1(x) = (x + 1)/(x - 2)

y-1 = 2(x-3) y-1 = 2x-6 y = 2x-6+1 y = 2x-5

eqn 1 Y = 2X + 6 eqn 2 2X - Y = 2 Rearrange eqn2 to isolate Y eqn2 Y = 2X - 2 so 2X + 6 = 2X - 2 subtracting 2X from both sides we get 6 = -2 As this is impossible this set of equations can not be solved.

There are infinitely many solutions. These are coordinates of all points on the line given by the equation 2 - y = 2x - 1 or 2x + y = 3.

y = 2x + 1 1. Make a table: x = -2; y = -3y = 2x + 1y = 2(-2) + 1 = -4 + 1 = -3 x = -1; y = -1y = 2x + 1y = 2(-1) + 1 = -2 + 1 = -1x = 0; y = 1y = 2x + 1y = 2(0) + 1 = 0 + 1 = 1 x = 1; y = 3y = 2x + 1y = 2(1) + 1 = 2 + 1 = 3 x = 2; y = 5y = 2x + 1y = 2(2) + 1 = 4 + 1 = 5 2. Plug the points (-2, -3), (-1, -1), (0, 1), (1, 3), and (2, 5) in a xy-coordinate system. 3. Draw a line which passes through those points. Thus, the line drawn is the graph of the function y = 2x + 1

2x-4y = 8 2x = 4y + 8 2x - 8 = 4y 2x/4 - 8/4 = y (1/2)x - 2 = y So, y = (1/2)x - 2, where 1/2 is the slope and -2 is the y-intercept :)

Slope-Intercept Form: y = -2x +1

y = -1/(3x7 + 2x - 9)y = -(3x7 + 2x - 9)-1y' = -(-1)(3x7 + 2x - 9)-2(3x7 + 2x - 9)'y' = (3x7 + 2x - 9)-2(21x6 + 2)y' = (21x6 + 2)/(3x7 + 2x - 9)2